Active control of a black hole or concentrator for flexural waves in an elastic metamaterial plate. (March 2020) - Ning, Li; Wang, Yi-Ze; Wang, Yue-Sheng
Highlights: A broadband flexural wave black hole equipment or concentrator is designed. The piezoelectric transducer patches connected by external electrical circuits are used as the active components. The experiments are performed to present the comparisons with the numerical simulations. Abstract: The black hole equipment or concentrator plays an important role in harnessing the wave energy, which has the potential application in the energy collecting engineering. In this work, we propose a broadband flexural wave black hole equipment or concentrator which is designed by the coordinate transformation method and active control systems. The concentrator with 48 alternative sectorial layers has a good concentrating performance. The polydimethylsiloxane (PDMS) and piezoelectric transducer (PZT) patches connected by external electrical circuits are used as the active components of the flexural wave concentrating configuration. By finite element simulations and experiments, the results show that the effective frequency region of the flexural wave concentrator without the active control systems is from 800 Hz to 1500 Hz. In addition, a wider frequency region of the concentrating performance from 800 Hz to 2000 Hz can be obtained by the active control system connected with external resistors and negative capacitor circuits. Furthermore, experiments are performed to show the excellent agreement with the numerical predictions. Graphical abstract: The black hole or concentrator of flexural waves with the active control action. Image, graphical abstract